2009
DOI: 10.1002/chem.200801837
|View full text |Cite
|
Sign up to set email alerts
|

The Bis(pentafluoroethyl)phosphinous Acid (C2F5)2POH

Abstract: The industrial product (C(2)F(5))(3)PF(2) is transformed into the phosphinic acid chloride (C(2)F(5))(2)P(O)Cl, which reacts with an excess of Bu(3)SnH in a clean, multistep reaction to give the stannyl derivative (C(2)F(5))(2)POSnBu(3). Subsequent treatment with gaseous HBr leads to the formation of (C(2)F(5))(2)POH, which is isolated in 70 % yield. Besides (CF(3))(2)POH, bis(pentafluoroethyl)phosphinous acid, (C(2)F(5))(2)POH, represents the second known example of a phosphinous acid that is predicted by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…31 P and 19 F NMR spectra of the acids agree with the literature values. 11,13 31 P NMR monitoring of the reaction of C 2 F 5 MgCl with OvPCl 3 indicates the presence of a pentet at δ 21.8 ppm ( 2 J P-F = 96 Hz), while the 19 F NMR spectrum showed a broad singlet at δ −79.9 and a doublet at δ −121.3 ppm.…”
Section: Resultssupporting
confidence: 86%
“…31 P and 19 F NMR spectra of the acids agree with the literature values. 11,13 31 P NMR monitoring of the reaction of C 2 F 5 MgCl with OvPCl 3 indicates the presence of a pentet at δ 21.8 ppm ( 2 J P-F = 96 Hz), while the 19 F NMR spectrum showed a broad singlet at δ −79.9 and a doublet at δ −121.3 ppm.…”
Section: Resultssupporting
confidence: 86%
“…It could be concluded that electron-donating substituents (alkyl group) and oxygen-containing groups (hydroxyl and methoxy) stabilized the phosphine oxide tautomer and strong electron-withdrawing substituent (halogens) stabilized the phosphinous acid tautomer. These results were in accordance with those of the previous reports [8,9]. Considering energy À6 in this case.…”
Section: Simple and Dimer Tautomerismsupporting
confidence: 96%
“…It is important to know that the share of each tautomer is different when the connected groups to the phosphorus atom are changed. In the reported studies, it has been shown that electron-donating alkyl and aryl groups stabilize the phosphine oxide tautomer while electron-withdrawing substituents, such as trifluoromethyl, stabilize the phosphinous acid structure [9,10].…”
Section: Introductionmentioning
confidence: 97%
“…[5] Shifting the tautomeric equilibrium towards the unusual form of a phosphinous acid can also be achieved by the introduction of electron-withdrawing substituents, such as trifluoromethyl-and pentafluoroethyl groups. [6,7] The employAbstract: Secondary phosphane oxides, R 2 P(O)H, are commonly used as preligands for transition-metal complexes of phosphinous acids, R 2 PÀOH (R = alkyl, aryl), which are relevant as efficient catalysts in cross-coupling processes. In contrast to previous work by other groups, we are interested in the ligating properties of an electron-deficient phosphinous acid, (R f ) 2 PÀOH, bearing the strongly electron-withdrawing and sterically demanding 2,4-bis(trifluoromethyl)phenyl group towards catalysisrelevant metals, such as palladium and platinum.…”
Section: Introductionmentioning
confidence: 99%